1995
DOI: 10.1073/pnas.92.7.2607
|View full text |Cite
|
Sign up to set email alerts
|

Fate of a redundant gamma-globin gene in the atelid clade of New World monkeys: implications concerning fetal globin gene expression.

Abstract: Conclusive evidence was provided that y', the upstream of the two linked simian y-globin loci (5'-y'-'y2-3'), is a pseudogene in a major group of New World monkeys. Sequence analysis of PCR-amplified genomic fragments of predicted sizes revealed that all extant genera of the platyrrhine family Atelidae [Lagothrix (woolly monkeys), Brachyteles (woolly spider monkeys), Ateles (spider monkeys), and Alouafta (howler monkeys)] share a large deletion that removed most of exon 2, all of intron 2 and exon 3, and much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Fitch et al (1991) suggested that the initial gene duplication event was followed by divergence of e and c for different ''embryonic niches.'' Later (35 to 55 MYA), a second case of genetic co-option occurred when embryonically expressed c was recruited for fetal expression in the early simian lineage Tagle et al 1988;Meireles et al 1995;Johnson et al 1996). The objective of our analysis was, first, to test for divergence in selective pressure between e and c and, second, to identify sites consistent with this type of selective pressure if they existed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fitch et al (1991) suggested that the initial gene duplication event was followed by divergence of e and c for different ''embryonic niches.'' Later (35 to 55 MYA), a second case of genetic co-option occurred when embryonically expressed c was recruited for fetal expression in the early simian lineage Tagle et al 1988;Meireles et al 1995;Johnson et al 1996). The objective of our analysis was, first, to test for divergence in selective pressure between e and c and, second, to identify sites consistent with this type of selective pressure if they existed.…”
Section: Discussionmentioning
confidence: 99%
“…Here we describe a model that allows variation in d N /d S among sites, with a fraction of sites evolving under divergent selective pressures between two clades following a co-option event. We implement the model in the maximum likelihood framework and apply it to two cases of evolution by gene duplication: (i) the e and c globin gene family (Meireles et al 1995;Johnson et al 1996;Fitch et al 1991) and (ii) the eosinophil cationic protein (ECP) and eosinophil-derived neurotoxin (EDN) gene family (Zhang et al 1998;Zhang and Rosenberg 2002).…”
Section: Introductionmentioning
confidence: 99%
“…All genes in this cluster have three exons and two introns (Lawn et al, 1980). In the atelids, γ 1 is a pseudogene (Meireles et al, 1995(Meireles et al, , 1998, whereas in the platyrrhine genera Aotus and Saimiri, the two loci are combined into a hybrid gene (Chiu et al, 1996).…”
Section: Kb Deletion In Atelinesmentioning
confidence: 99%
“…In the present study, sequences of the γ 1 -globin pseudogene were used in a molecular analysis of the phylogenetic relationships among Brazilian howler monkeys. The aligned sequences were also used to estimate divergence times based on a local molecular clock, and to investigate the presence of the Alu insertion -found in other Alouatta species (Meireles et al, 1995(Meireles et al, , 1998 …”
Section: Kb Deletion In Atelinesmentioning
confidence: 99%
See 1 more Smart Citation